2023
DOI: 10.1002/ece3.10400
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod effects in a freshwater community: Amphibian larvae develop faster and zooplankton abundance increases under an early‐season photoperiod

Abstract: Organisms that shift their phenologies in response to global warming will experience novel photic environments, as photoperiod (daylength) continues to follow the same annual cycle. How different organisms respond to novel photoperiods could result in phenological mismatches and altered interspecific interactions. We conducted an outdoor mesocosm experiment exposing green frog (Rana clamitans) larvae, gray treefrog (Hyla versicolor) larvae, phytoplankton, periphyton, and zooplankton to a three‐month shift in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…We also added approximately 20 grams of alfalfa rabbit food (Oxbow brand) as an initial food source for larvae on 21 June 2022. To understand how photoperiod affected food availability for gray treefrog larvae, we assessed phytoplankton and zooplankton abundances on 7 July 2022, following the methods of Stoler et al [48] and Neptune & Benard [37]. Briefly, we measured chlorophyll a fluorescence of four 1 litre water samples collected from each mesocosm using an Aquafluor® fluorometer (Turner Designs, Inc.).…”
Section: Materials and Methods (A) Aquatic Field Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also added approximately 20 grams of alfalfa rabbit food (Oxbow brand) as an initial food source for larvae on 21 June 2022. To understand how photoperiod affected food availability for gray treefrog larvae, we assessed phytoplankton and zooplankton abundances on 7 July 2022, following the methods of Stoler et al [48] and Neptune & Benard [37]. Briefly, we measured chlorophyll a fluorescence of four 1 litre water samples collected from each mesocosm using an Aquafluor® fluorometer (Turner Designs, Inc.).…”
Section: Materials and Methods (A) Aquatic Field Experimentsmentioning
confidence: 99%
“…While the direct effects of photoperiod on development have been investigated thoroughly in taxa such as insects, very few studies examine how photoperiod affects amphibian metamorphosis and growth [34][35][36][37]. Experiments using treatments with static, unchanging photoperiods demonstrate that larval growth or development rate is affected by photoperiod [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies on Fugu rubripes (Takifugu rubripes) revealed that the growth of larvae after 19 days of hatching was enhanced under conditions of 20 h of daylight exposure each day [23]. Conversely, reduced duration of light exposure in the photoperiod accelerated the development and metamorphosis rate of green frog (Rana clamitans) and gray treefrog (Hyla versicolor) tadpoles [24]. The growth of crustaceans often coincides with their molting behavior.…”
Section: Introductionmentioning
confidence: 99%